2017
DOI: 10.1111/jora.12324
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Transmission of Conflict Management Styles Across Inter‐Parental and Adolescent Relationships

Abstract: This study longitudinally investigated transmission of conflict management styles across inter‐parental, adolescent–parent, adolescent–friend, and adolescent–partner relationships. During four waves, 799 middle‐to‐late adolescents (Mage‐t1 = 15.80; 54% boys) and their parents completed the Conflict Resolution Style Inventory. Cross‐lagged path analyses indicated transmission of adolescent conflict management styles in relationships with parents to relationships with friends and romantic partners: Positive prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 51 publications
(114 reference statements)
0
22
0
2
Order By: Relevance
“…Soenens et al (2007) found evidence suggesting that intergenerational transmission of empathy-related responding, a construct which is closely tied to CfO and suggests that CfO might also be transmitted between generations. Furthermore, Staats et al (2017) found evidence in a longitudinal study for intergenerational transmission of conflict management styles, such that adolescents' conflict resolution strategies with their parents predicted their conflict resolution strategies with friends and romantic partners. As conflict resolution strategies have been shown to be closely related to CfO (Feher 2016), it is plausible that CfO is also developed via intergenerational transmission and that it could have significant effects on close relationships in an individual's life.…”
Section: Limitations and Future Directionsmentioning
confidence: 93%
“…Soenens et al (2007) found evidence suggesting that intergenerational transmission of empathy-related responding, a construct which is closely tied to CfO and suggests that CfO might also be transmitted between generations. Furthermore, Staats et al (2017) found evidence in a longitudinal study for intergenerational transmission of conflict management styles, such that adolescents' conflict resolution strategies with their parents predicted their conflict resolution strategies with friends and romantic partners. As conflict resolution strategies have been shown to be closely related to CfO (Feher 2016), it is plausible that CfO is also developed via intergenerational transmission and that it could have significant effects on close relationships in an individual's life.…”
Section: Limitations and Future Directionsmentioning
confidence: 93%
“…Parent–child recurring conflict refers to frequent, serious arguments between parents and children on the same topics with no resolution (Conger et al., 2011). From a social learning perspective, children learn behaviors through observation and interaction with parents, which later generalizes to their interactions with others (Bandura & National Institute of Mental Health, 1986; Staats et al., 2017). In contexts of high parent–child recurring conflict, children may learn and engage in maladaptive conflict resolution skills such as more deviant (e.g., breaking an item) and less problem‐solving (e.g., considering consequences; Staats et al., 2017; Van Doorn, Branje, & Meeus, 2011) behaviors.…”
Section: Parental Anger Managementmentioning
confidence: 99%
“…From a social learning perspective, children learn behaviors through observation and interaction with parents, which later generalizes to their interactions with others (Bandura & National Institute of Mental Health, 1986; Staats et al., 2017). In contexts of high parent–child recurring conflict, children may learn and engage in maladaptive conflict resolution skills such as more deviant (e.g., breaking an item) and less problem‐solving (e.g., considering consequences; Staats et al., 2017; Van Doorn, Branje, & Meeus, 2011) behaviors. Adolescents who experience low parent–child conflict may observe and model parents' conflict resolution or problem‐solving strategies such as compromising (Conger et al., 2011; Goddard et al., 2004).…”
Section: Parental Anger Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a large body of literature indeed suggesting that especially in the early developmental stages children may observe the relational behavior of their parents, and subsequently these experiences are assumed to form the basis for relationships with siblings and peers (Conger et al, 2000; Cui & Fincham, 2010; De Goede, Branje, van Duin, VanderValk, & Meeus, 2012). Later in life, these experiences provide a basis for the quality of relationships with intimate partners (e.g., Staats, van der Valk, Meeus, & Branje, 2017), and (mal)functioning in a variety of other life domains (see, for example, Collins & Steinberg, 2006; Dirks et al, 2015; Kim et al, 1999).…”
Section: Theoretical Perspectivesmentioning
confidence: 99%